ISU GENDER DALAM MANAJEMEN BENCANA DAN LINGKUNGAN DI INDONESIA - Syarkawi Syarkawi; Muhammad Akbar Maulana (Ensiklopedia Social Review, 2025)
Barious disasters in indonesia, such as the 2004 tsunami in aceh and the 2010 eruption of mount merapi, have impacted men and women differently. Gender issues are a crucial aspect of disaster and environmental management in indonesia, considering the high vulnerability of women and marginalized groups to disaster impacts, such as difficulties in accessing healthcare facilities and adequate shelters, as well as the increased risk of gender-based violence during disaster recovery periods. This study aims to examine gender issues in disaster and environmental management in indonesia. It employs a descriptive qualitative research method with a literature review approach, where the researchers collect, analyze, and interpret information from various written sources, such as government reports, academic studies, and publications from non-governmental organizations. The findings reveal that gender inequality often exacerbates the impact of disasters on women, such as increased rates of gender-based violence in evacuation shelters or limited access to humanitarian aid. Meanwhile, their involvement in decision-making processes, for instance, during emergency response and post-disaster recovery, remains minimal.Keywords: Gender Issues, Disaster Management, Environment.